2000
DOI: 10.1177/1358836x0000500303
|View full text |Cite
|
Sign up to set email alerts
|

Spurious systolic hypertension in youth

Abstract: Six young men diagnosed with systolic hypertension had normal carotid pressure wave contours, normal synthesized aortic pressure wave contours and normal diastolic and mean pressures in upper limb arteries. Elevated brachial systolic pressure was caused by a high narrow systolic peak of the pressure wave. This was attributed to amplification of the pressure wave between the ascending aorta and upper limb (radial and brachial) arteries that is associated with attainment of full body length and very distensible … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
98
0
5

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 139 publications
(111 citation statements)
references
References 14 publications
(20 reference statements)
8
98
0
5
Order By: Relevance
“…However, the mean age of our study population was 27.8 7 3.7 years and, thus, widely eliminating age-related changes of the cardiovascular system. While cardiovascular phenomena such as spurious systolic hypertension have been reported in young individuals, 42 we believe that our study population ranging from 23 to 35 years also remains largely unaffected by such maturational changes during growth.…”
Section: Discussionmentioning
confidence: 91%
“…However, the mean age of our study population was 27.8 7 3.7 years and, thus, widely eliminating age-related changes of the cardiovascular system. While cardiovascular phenomena such as spurious systolic hypertension have been reported in young individuals, 42 we believe that our study population ranging from 23 to 35 years also remains largely unaffected by such maturational changes during growth.…”
Section: Discussionmentioning
confidence: 91%
“…Such a phenomenon might be more common in tall subjects with low aortic pulse wave velocity, and therefore might be more common in young adult males than in young adult females because the former tend to be taller. 10 It has also been shown 11 that the arteries of young subjects with ISH, far from being stiff, tend to be highly elastic (nonsmokers and athletes). This is the background to the idea of 'spurious' or 'pseudo'-systolic hypertension in young men.…”
Section: Discussionmentioning
confidence: 99%
“…O'Rourke found that ISH is 'not uncommon' in young healthy adults of between 15 and 25 years of age 10 and Mahmoud and Feely 11 found a prevalence of 12.6% in a population of 174 healthy, male medical students.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the phenomenon of spurious systolic hypertension, that is, the disproportional increase of brachial SBP with low aortic SBP has been repeatedly described in youths. 33 This phenomenon is related to the complex arterial mechanical properties (wave reflections, their timing and anthropometric parameters that is, height) and it may be potentially explained by the presence of low pressure wave reflections in the presence of obesity. 34 Finally, it should be stated that the present results may have been modulated by (i) the fact that the normal ranges of HBP have been derived from the same population, 24 whereas OBP cutoffs are based on international guidelines; 35 and (ii) the fact that OBP thresholds are based on the auscultatory method compared with the oscillometric devices that were used in this study.…”
Section: Perspectives and Limitationsmentioning
confidence: 99%